A Two-Year-Old Boy with Diphallia and Multiple Congenital Anomalies - Rizal Trianto; Pradana Nurhadi; Besut Daryanto (Jurnal Kedokteran Brawijaya, 2022)
Diphallia is a rare urogenital defect and varies from a small accessory penis or duplication of the glans to complete penile duplication. Its incidence is 1 in 5.5 million live births. Only 100 cases were reported from 1609 until 2021. A two-year-old boy with diphallia and multiple congenital anomalies had an uncircumcised penis with two glans penis and two complete urethral orifices, accompanied by scrotum bifidum, asymmetric right buttock, with normal anorectal position. Spina bifida with lipomyelocele, tethered cord at the level of vertebra lumbar 3-4, scrotum bifidum, and left mild hydronephrosis were observed using Magnetic Resonance Imaging (MRI). Urethrocystoscopy of both complete urethra revealed meatal stenosis and bulbar urethral stricture, normal posterior urethral, and no verumontanum in the right urethral orifice and did dilatation. Whereas normal urethral orifice, anterior urethra, posterior urethra and verumontanum were found in the left side. Management for diphallia must consider associated anomalies and the goal of patient satisfaction. In this case, conservative treatment is the best choice.